Simultaneous Determination of 9 Mycotoxins in Fruits by Ultra-performance Liquid Chromatography-Tandem Mass Spectrometry - Yang NI; Junjun YANG; Lei SHI; Yingying ZHANG; Rong XIONG (Shipin gongye ke-ji, 2022)
An ultra-performance liquid chromatography-tandem mass spectrometry method was developed for the simultaneous determination of 9 mycotoxins in fruit. Sample extraction, purification conditions and instrument conditions were optimized. The samples were ultrasonic extracted with 10 mmol/L citric acid acetonitrile solution and salted out by adding NaCl. After centrifugation, the supernatant was cleaned up by C18 sorbent and separated on an ACQUITY UPLC BEH C18 column. The analytes were detected in the multiple reaction monitoring mode after being ionized by an electrospray positive ion. Quantitative analysis was performed by the external standard method using matrix-matched calibration curves. The results showed that all the 9 mycotoxins were well separated in 5 min. The coefficients of determination (R2) were greater than 0.999, suggesting good linearity of the method in the mass concentration range. The method limits of detection (3S/N) and limits of quantification (10S/N) were 0.004~1.676 μg/kg and 0.014~5.587 μg/kg, respectively. The recovery experiments were performed with peach and cherry samples at three spiked levels (low, medium and high) were 84.5%~113.2% with the relative standard deviations were 0.7%~4.0% (n=6). This method was used to analyze the contamination status of 9 mycotoxins in fruit samples (strawberry, cherry, grape, apple and pear). The results showed that beauvericin, patulin and Altenuene toxins were found in cherry and grape samples, and their contents were ranged from ND (not detected) ~12.47 µg/kg. The method is proved to be stable, accurate, sensitive and rapid, and can meet the requirements for the analysis of 9 mycotoxins residues in a variety of fruit samples.